Abnormal crystal growth in CH3NH3PbI3−xClx using a multi-cycle solution coating process1. Issue 8 (29th August 2015) - Dong, Qingfeng; Yuan, Yongbo; Shao, Yuchuan; Fang, Yanjun; Wang, Qi; Huang, Jinsong
<x xml:space="preserve">Abstract</x> Multi-cycle coating of mixed halide perovskite films by incorporating Cl in precursors induces abnormal grain growth with appearance of very large grains.